UI/UX Design for Mobile-based Sports Instructor Search Application “Befind” using Design Thinking - Cahyadi, Kadek Wawan; Indradewi, I Gusti Ayu Agung Diatri; Pratiwi, Putu Yudia (Sistemasi: Jurnal Sistem Informasi, 2023)
BeFind is a website-based application that facilitates the public and sports instructors to be able to interact and transact with each other. However, the website has deficiencies such as incomplete features and inflexible use, so it is necessary to design a mobile-based application to optimize the features. The purpose of this research is to produce UI and UX model designs that apply the Design Thinking method and to find out the results of usability testing. Design Thinking is a product design process resulting from problem-solving efforts that arise from potential product users. Empathy stage, conduct interviews to get problems. The define stage is carried out by creating a user persona from the results of the interview. The ideate stage is carried out by brainstorming to compile user flow. The prototype stage is made in the form of a mockup design and a prototype design is prepared. The test phase was carried out to test the design with task scenarios on 4 usability aspects and 1 aspect using the System Usability Scale (SUS) questionnaire. In the final test for service seekers and service providers respondents obtained 97% and 96% learnability results, efficiency 0.033689182 goals/sec and 0.033689182 goals/sec, 96% and 95% memoryability, 0.0306 and 0.0800 errors, and satisfaction with SUS obtained 94 results with the best imaginable predicate. In efficiency there is a decrease in yield caused by a bad signal factor. The resulting UI and UX can become the foundation for development of the "BeFind" mobile application based on the prototype design that has been designed in this study.